Allergic contact dermatitis to shoes: contribution of a specific series to the diagnosis - Rosana Lazzarini; Rodolfo Ferreira Mendonça; Mariana de Figueiredo Silva Hafner (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: In our country, the Brazilian Standard Series is the most used for the etiological diagnosis of allergic contact dermatitis to shoes. However, there is no assessment of the usefulness of specific allergens for shoes. Objectives: To measure the improvement in diagnostic accuracy of allergic contact dermatitis to shoes with the use of a specific complementary series in patch testing and describe the characteristics of the affected population, such as gender, location of lesions, time of evolution, and the most common allergens. Methods: This retrospective study evaluated the results of 52 patients with suspected shoe dermatitis subjected to patch tests with the standard and specific series to quantify the gain in diagnostic accuracy. Results: Among the 52 suspected cases, 29 cases (56%) were confirmed. In 13 (45%) cases the diagnosis was determined through the specific series, which results in an 81% increase in the number of diagnoses. Study limitation: Small sample size. Conclusions: Women were more commonly affected, with a mean time for the final diagnosis of 45 months, and the most common localization was the dorsum of the feet. There was an increase in diagnostic accuracy with the introduction of new haptens in the patch test of patients with suspected shoes dermatitis.